Wykorzystanie uogólnionej miary odległości do oceny stopnia popularności giełdowych instrumentów pochodnych - Majewska, Agnieszka (Classification of Derivatives Quoted on World Exchanges Using Generalised Distance Measure, 2005)
The main goal of the article is to show which derivatives quoted on world exchanges were the most popular in 2002 and 2003. For this purpose stock, index, interest rate, currency and commodity options and futures were classified. Generalised Distance Measure was the method of classification in this research. The activity of investors on derivatives markets was measured by three variables: volume traded, underlying value and open interest. Received results show that interest rate futures, stock options and interest rate options were the most popular derivatives in the world, such as in Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 220-227